Non-porous diaphragm and lithium battery

By coating 5~15% sulfonic acid polyamide solution on the lithium battery separator, the problem of maintaining high ionic conductivity while inhibiting the growth of lithium dendrites is solved, and the high circulation performance and safety of lithium batteries are achieved.

CN119231091BActive Publication Date: 2025-03-28ANHUI LIKE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411754893.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-28
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

While inhibiting the growth of lithium dendrites, the existing lithium battery separators are difficult to maintain high ionic conductivity and heat resistance, which affects the cycling performance and safety of the battery.

Method used

A non-porous separator is used, which consists of a base film and a coating layer. The coating layer contains 5-15% sulfonic acid polyamide solution. A sulfonic acid polyamide solution is prepared by a specific preparation method to enhance its binding force with metal ions, thereby increasing the migration number and conductivity of lithium ions.

Benefits of technology

Effectively inhibit the growth of lithium dendrites, improve the circulation and electrochemical performance of lithium batteries, and improve the safety of batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119231091B_ABST
    Figure CN119231091B_ABST
Patent Text Reader

Abstract

The present invention discloses a non-porous diaphragm and a lithium battery. The non-porous diaphragm comprises: a base film, a coating layer, the coating layer is formed on the base film, and the coating layer comprises a sulfonic acid polyamide solution with a solid content of 5 to 15%. The sulfonic acid group is a strong acidic group with high polarity and high hydrophilicity, so that it can form a stable coordination compound or complex with a variety of metal ions. The oxygen atom in the sulfonic acid group contains lone pairs of electrons, and these lone pairs of electrons can enter the empty orbit of the metal ion to form a coordination bond. This coordination effect enhances the binding force between the sulfonic acid group and the metal ion. When it is introduced into the polyamide monomer polymerization to obtain the aramid material, it is then coated on the lithium ion battery diaphragm so that it can act as an ion transition site to obtain a non-porous diaphragm, which can improve the ionic conductivity, greatly improve the lithium ion migration number and its transmission efficiency in the battery, and inhibit the growth of lithium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery separators, and in particular to a non-porous separator and a lithium battery. Background Art

[0002] As global energy is gradually consumed, available non-renewable energy will become less and less, and the continuous use of non-renewable energy will bring challenges to the environment. Sustainable energy has the advantages of sustainable use, environmental friendliness, safety and convenience, and lithium batteries have attracted much attention in sustainable energy.

[0003] As the lithium-ion battery market continues to expand, the demand for battery capacity and energy density is also increasing. In this context, lithium metal anodes have attracted much attention due to their high theoretical capacity and low redox potential, but this type of anode has not yet been put into practical use. Because during the charging process, lithium dendrites will form on the metal surface. When the dendrites grow to a certain extent, they may pierce the diaphragm, causing thermal runaway and short circuit, reducing battery safety. Lithium dendrites grow along the diaphragm gaps and form lithium dendrites when they contact the positive electrode. Therefore, removing the diaphragm pores can prevent their growth, but it will greatly reduce the lithium ion permeability and affect the charge and discharge rate.

[0004] For lithium metal batteries with high energy density, the separator design must be able to inhibit the growth of lithium dendrites, maintain ionic conductivity, and have high heat resistance and thermal stability. Therefore, the existing lithium battery separators still need to be improved. Summary of the invention

[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a non-porous separator and a lithium battery, wherein the non-porous separator can increase the number of lithium ion migration and inhibit the growth of lithium dendrites, and the application of the non-porous separator in a lithium battery can improve the cycle performance of the lithium battery.

[0006] In one aspect of the present invention, the present invention provides a non-porous membrane, the non-porous membrane comprising:

[0007] Basement membrane,

[0008] A coating layer, wherein the coating layer is formed on the base film, and the coating layer comprises a sulfonic acid polyamide solution having a solid content of 5 to 15%;

[0009] The preparation method of the sulfonic acid polyamide solution comprises:

[0010] (1) Under the protection of inert gas, the meta-diamine and the para-diamine are dissolved in an organic solvent and stirred to form a sulfonated diamine suspension, the temperature is raised to 60-70°C, and then a base is added to form a sulfonated ammonium diamine salt, and then the temperature is lowered to -10-0°C to obtain a clear sulfonated ammonium diamine salt solution;

[0011] (2) mixing the first portion of the acyl chloride with the ammonium sulfonate diamine solution at a temperature of -10 to 15° C. to react to obtain a prepolymer solution;

[0012] (3) The prepolymerization solution is filtered, and then a second portion of acid chloride is added to obtain a sulfonic acid polyamide solution.

[0013] A sulfonic acid polyamide solution with a solid content of 5-15% is coated on the base film. The sulfonic acid group is a strong acidic group with high polarity and high hydrophilicity, which enables it to form stable complexes or complexes with a variety of metal ions. The oxygen atoms in the sulfonic acid group contain lone pairs of electrons, which can enter the empty orbits of metal ions to form coordination bonds. This coordination effect enhances the binding force between the sulfonic acid group and the metal ion. When it is introduced into the polyamide monomer polymerization to obtain the aramid material, it is then coated on the lithium-ion battery separator so that it can act as an ion transition site to obtain a non-porous separator, which can improve the ionic conductivity, greatly improve the lithium ion migration number and its transmission efficiency in the battery, and inhibit the growth of lithium dendrites.

[0014] In the process of preparing the sulfonic acid polyamide solution, the sulfonic acid ammonium salt diamine solution is first prepared, and then the first portion of the acyl chloride is mixed with the sulfonic acid ammonium salt diamine solution to obtain a prepolymer solution, and then the prepolymer solution is filtered to remove the hydrochloride insoluble in the solvent. Because there is material loss in the filtration process, in order to ensure the accuracy of the subsequent feeding amount, the weight of the filtered solution needs to be weighed, and the next step feeding amount is reduced according to the loss ratio. On the one hand, since the furanyl chloride bond angle is 131°, which is different from the aromatic acyl chloride bond angle of 180° or 120°, it will cause it to be polymerized with the para-diamine or meta-diamine alone at low temperature. With the increase of chain length, the steric hindrance increases significantly, making the solubility of the generated prepolymer unsatisfactory or the reaction activity reduced, and finally resulting in the polymerization degree of the sulfonic acid polyamide solution is unsatisfactory; on the other hand, the conjugation effect of the furan ring is much smaller than that of the aromatic ring, resulting in a significant decrease in the activity of the rear end group after the chain length increases, affecting further polycondensation. Therefore, when furan dicarboxylic acid chloride is polymerized with para-diamine or meta-diamine alone, the polymerization degree is low, and it is difficult to obtain a polyamide solution with a desired molecular weight or viscosity. The present invention uses para-diamine and meta-diamine to participate in the polymerization reaction at the same time, and controls the molar ratio of the two to be close to 1:1, so that they are randomly copolymerized with furan diamine, which solves the problems of steric hindrance and end group activity and greatly increases the upper limit of the polymerization degree.

[0015] In addition, the non-porous diaphragm according to the present invention may also have the following additional technical features:

[0016] In some embodiments of the present invention, in step (1), the molar ratio of the para-diamine to the meta-diamine is 1:(1.05-0.95).

[0017] In some embodiments of the present invention, in step (1), the ratio of the mass of the organic solvent to the total mass of the para-diamine and the meta-diamine is (6-10):1.

[0018] In some embodiments of the present invention, in step (1), the ratio of the amount of the base substance to the total amount of the para-diamine and the meta-diamine substance is (2-2.5):1.

[0019] In some embodiments of the present invention, in step (2), the ratio of the amount of the first acyl chloride to the total amount of the para-diamine and the meta-diamine is (0.97-1.0):1.

[0020] In some embodiments of the present invention, the molar ratio of the second acyl chloride to the first acyl chloride is (0.01-0.05):1.

[0021] In some embodiments of the present invention, the inert gas is one or more of nitrogen, helium and argon; the organic solvent is one or more of toluene, N,N-dimethylacetamide, N-methylpyrrolidone and N,N-dimethylformamide; the base is one or more of triethylamine, dimethylethanolamine and triethylenediamine; the acyl chloride includes at least one of 2,5-furandicarboxylic acid chloride, isophthaloyl chloride and terephthaloyl chloride.

[0022] In some embodiments of the present invention, the para-diamine is 2,5-diaminobenzenesulfonic acid; and the meta-diamine is 2,4-diaminobenzenesulfonic acid.

[0023] In some embodiments of the present invention, in step (2), the viscosity of the prepolymer solution is 80-120 cp, the reaction time is 1-2.5 h, and the reaction temperature is 0-18° C.

[0024] In some embodiments of the present invention, the viscosity of the sulfonic acid polyamide solution is 200-5000 cp.

[0025] In a second aspect of the present invention, the present invention provides a lithium-ion battery, wherein the separator in the lithium-ion battery adopts the above-mentioned non-porous separator, so that the cycle performance of the lithium battery is improved.

[0026] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0028] Figure 1 The electrochemical impedance spectra of the PP diaphragm of the comparative example of the present invention and the non-porous diaphragm sample No. 1, the non-porous diaphragm sample No. 2 and the non-porous diaphragm sample No. 3 prepared in Example 1 under the electrolyte conditions;

[0029] Figure 2 These are electrochemical impedance spectra of non-porous membrane sample No. 1, non-porous membrane sample No. 2, and non-porous membrane sample No. 3 prepared in Example 1 of the present invention in the absence of an electrolyte;

[0030] Figure 3 This is a graph showing the ion migration number results of the non-porous membrane sample No. 1 in Example 1 of the present invention;

[0031] Figure 4 This is a graph showing the ion migration number results of the non-porous membrane sample No. 2 in Example 1 of the present invention;

[0032] Figure 5 This is a graph showing the ion migration number results of the non-porous membrane sample No. 3 in Example 1 of the present invention;

[0033] Figure 6 It is a graph showing the ion migration number results of the PP diaphragm in the comparative example of the present invention. DETAILED DESCRIPTION

[0034] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way. Example 1

[0035] 1. Preparation of sulfonic acid polyamide solution:

[0036] (1) Under nitrogen protection, 48.7719 g of 2,5-diaminobenzenesulfonic acid and 48.7719 g of 2,4-diaminobenzenesulfonic acid were dissolved in 561.9 g of N,N-dimethylacetamide and stirred to form a sulfonated diamine suspension, the temperature was raised to 61°C, and then 104.893 g of triethylamine was added, and the mixture was stirred for 10 minutes to form a sulfonate ammonium diamine solution, and then the temperature was lowered to 0°C to obtain a clear sulfonate ammonium diamine solution;

[0037] (2) At -0°C, 100 g of 2,5-furandicarbonyl chloride was mixed with the above-mentioned ammonium sulfonate diamine solution, and the mixture was stirred for reaction for 20 minutes to obtain a prepolymer solution;

[0038] (3) The prepolymer solution was filtered, and then 1.1438 g of 2,5-furandicarboxylic acid chloride was added to obtain a sulfonic acid polyamide solution with a viscosity of 4200 cp.

[0039] 2. Preparation of non-porous diaphragm:

[0040] Sample No. 1: The sulfonic acid polyamide solution prepared above was diluted to a solid content of 8%, and then coated on a PP base film. After washing and drying, a non-porous diaphragm PP base film sample No. 1 was prepared, recorded as sample No. 1.

[0041] Sample No. 1 # The sulfonic acid polyamide solution prepared above was diluted to a solid content of 8%, and then coated on a PE base film. After washing and drying, a non-porous diaphragm No. 1 PE base film sample was prepared, which was recorded as sample No. 1. # .

[0042] Sample No. 2: The sulfonic acid polyamide solution prepared above was diluted to a solid content of 12%, and then coated on a PP base film. After washing and drying, a non-porous diaphragm No. 2 PP base film sample was prepared, recorded as Sample No. 2.

[0043] Sample No. 2 # The sulfonic acid polyamide solution prepared above was diluted to a solid content of 12%, and then coated on a PE base film. After washing and drying, a non-porous diaphragm No. 2 PE base film sample was prepared, which was recorded as sample No. 2. # .

[0044] Sample No. 3: The sulfonic acid polyamide solution prepared above was diluted to a solid content of 15%, and then coated on the PP base film. After washing and drying, a non-porous diaphragm No. 2 PP base film sample was prepared, recorded as sample No. 3.

[0045] Sample No. 3 # The sulfonic acid polyamide solution prepared above was diluted to a solid content of 15%, and then coated on the PE base film. After washing and drying, a non-porous diaphragm No. 3 PE base film sample was prepared, which was recorded as No. 3 sample. # .

[0046] The air permeability of the six groups of samples was tested and the results showed that the gas permeability was 0 mL / min. No obvious pore structure was found under electron microscopy.

[0047] 3. Assembling batteries: Assemble button-type lithium-ion symmetrical batteries using the prepared non-porous separator samples No. 1, No. 2, and No. 3.

[0048] Electrochemical impedance test was performed on button-type lithium-ion symmetrical batteries. The test results are shown in Figure 1 ; Assemble button cells without electrolyte and perform electrochemical impedance test. The test results are shown in Figure 2 .

[0049] The ion migration number of the battery was tested by the steady-state current method. The lithium ion migration number of the battery obtained by sample No. 1 was 0.81. The test results are shown in Figure 3; The lithium ion migration number of the battery obtained from sample No. 2 is 0.73, and the test results are shown in Figure 4 ; The lithium ion migration number of the battery obtained from sample No. 3 is 0.77, and the test results are shown in Figure 5 . Example 2

[0050] 1. Preparation of sulfonic acid polyamide solution:

[0051] (1) Under nitrogen protection, 46.821 g of 2,5-diaminobenzenesulfonic acid and 50.7228 g of 2,4-diaminobenzenesulfonic acid were dissolved in 561.9 g of N-methylpyrrolidone and stirred to form a sulfonated diamine suspension, the temperature was raised to 61°C, and then 104.893 g of triethylamine was added, and the mixture was stirred for 10 minutes to form sulfonic acid ammonium diamine, and then the temperature was lowered to 0°C to obtain a clear sulfonic acid ammonium diamine solution;

[0052] (2) At 0°C, 100 g of terephthaloyl chloride was mixed with the above ammonium sulfonate diamine solution and stirred for reaction for 20 minutes to obtain a prepolymer solution;

[0053] (3) The prepolymer solution was filtered, and then 1.133 g of terephthaloyl chloride was added to obtain a sulfonic acid polyamide solution with a viscosity of 2300 cp.

[0054] 2. Preparation of non-porous diaphragm: The sulfonic acid polyamide solution prepared above was diluted to a solid content of 6%, and then coated on a PP base film. After washing and drying, a non-porous diaphragm was prepared. Example 3

[0055] 1. Preparation of sulfonic acid polyamide solution:

[0056] (1) Under nitrogen protection, 48.7719 g of 2,5-diaminobenzenesulfonic acid and 48.7719 g of 2,4-diaminobenzenesulfonic acid were dissolved in 749.2 g of N,N-dimethylacetamide and stirred to form a sulfonated diamine suspension, the temperature was raised to 61°C, and then 104.893 g of triethylamine was added, and the mixture was stirred for 10 minutes to form a sulfonate ammonium diamine solution, and then the temperature was lowered to 0°C to obtain a clear sulfonate ammonium diamine solution;

[0057] (2) At 0°C, 100 g of isophthaloyl chloride was mixed with the above ammonium sulfonate diamine solution and stirred for reaction for 20 minutes to obtain a prepolymer solution;

[0058] (3) The prepolymer solution was filtered, and then 0.9331 g of isophthaloyl chloride was added to react to obtain a sulfonic acid polyamide solution with a viscosity of 825 cp.

[0059] 2. Preparation of non-porous diaphragm: The sulfonic acid polyamide solution prepared above was diluted to a solid content of 6%, and then coated on a PP base film. After washing and drying, a non-porous diaphragm was prepared. Comparative Example

[0060] 1. The diaphragm is made of PP diaphragm.

[0061] 2. Assemble the battery: Assemble the prepared PP diaphragm into button-type lithium-ion symmetrical batteries, and perform electrochemical impedance test on the batteries. The test results are shown in Figure 1 The lithium ion migration number of the obtained battery is 0.31. The test results are shown in Figure 6 It can be seen that the lithium ion migration numbers of samples No. 1, 2, and 3 in Example 1 are significantly higher than that of the PP separator.

[0062] The samples No. 1, No. 2, No. 3 and No. 1 obtained in Example 1 were # , Sample No. 2 # and sample number 3 # The test was carried out under electrolyte conditions, and the corresponding results are shown in Table 1. The test was carried out under no electrolyte conditions, and the measured resistance values ​​and conductivity are shown in Table 2.

[0063] Table 1

[0064]

[0065] Table 2

[0066]

[0067] From the data in Table 1, it can be seen that the resistance value of the non-porous diaphragm prepared by the present invention is significantly reduced, and when the sulfonic acid polyamide solution is diluted to a certain solid content, the conductivity is improved. Figure 1-Figure 5 From the test results, it can be seen that the diaphragm of the present invention has the advantages of reducing interface impedance and improving the migration number of lithium-ion batteries, and the base film is effective for both PE film and PP film. Applying it in lithium batteries can improve the electrochemical performance of lithium batteries.

[0068] It can be seen from the data in Table 2 that in the absence of an electrolyte, the non-porous membrane prepared by the present invention can also achieve ion conductivity, indicating that the non-porous membrane itself has ion conductivity. After adding the electrolyte, the ion conductivity of the non-porous membrane is even stronger.

[0069] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0070] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A non-porous diaphragm, characterized in that: include: Basement membrane, A coating layer, wherein the coating layer is formed on the base film, and the coating layer comprises a sulfonic acid polyamide solution having a solid content of 6 to 15%; The preparation method of the sulfonic acid polyamide solution comprises: (1) Under the protection of inert gas, 2,4-diaminobenzenesulfonic acid and 2,5-diaminobenzenesulfonic acid in a molar ratio of 1:(0.95-1.05) are dissolved in an organic solvent and stirred to form a sulfonated diamine suspension, the temperature is raised to 60-70°C, and then a base is added to form sulfonic acid ammonium diamine, and then the temperature is lowered to -10-0°C to obtain a clear sulfonic acid ammonium diamine solution; (2) mixing the first portion of the acyl chloride with the ammonium sulfonate diamine solution at a temperature of -10 to 15° C. to react to obtain a prepolymer solution; (3) The prepolymerization solution is filtered, and then a second portion of acid chloride is added to obtain a sulfonic acid polyamide solution.

2. The non-porous membrane according to claim 1, characterized in that: In step (1), the ratio of the mass of the organic solvent to the total mass of the 2,4-diaminobenzenesulfonic acid and the 2,5-diaminobenzenesulfonic acid is (6-10):

1.

3. The non-porous membrane according to claim 1, characterized in that: In step (1), the ratio of the amount of the base substance to the total amount of the 2,4-diaminobenzenesulfonic acid and 2,5-diaminobenzenesulfonic acid is (2-2.5):

1.

4. The non-porous membrane according to claim 1, characterized in that: In step (2), the ratio of the amount of the first acyl chloride to the total amount of the 2,4-diaminobenzenesulfonic acid and 2,5-diaminobenzenesulfonic acid is (0.97-1.0):

1.

5. The non-porous membrane according to claim 1, characterized in that: The molar ratio of the second acyl chloride to the first acyl chloride is (0.01-0.05):

1.

6. The non-porous membrane according to claim 1, characterized in that The inert gas is helium or argon; the organic solvent is one or more of toluene, N,N-dimethylacetamide, N-methylpyrrolidone and N,N-dimethylformamide; the base is one or more of triethylamine, dimethylethanolamine and triethylenediamine; the acyl chloride includes at least one of 2,5-furandicarboxylic acid chloride, isophthaloyl chloride and terephthaloyl chloride.

7. The non-porous membrane according to claim 1, characterized in that In step (2), the viscosity of the prepolymer solution is 80-120 cp, the reaction time is 1-2.5 h, and the reaction temperature is 0-15° C.; In step (3), the viscosity of the sulfonic acid polyamide solution is 200-5000 cp.

8. A lithium battery, characterized in that: The lithium battery comprises the non-porous separator according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Production method and production system of lithium bis (fluorosulfonyl) imide

    CN115448268A

  • Water-based coating slurry, lithium battery diaphragm and preparation method of lithium battery diaphragm

    CN118867566A